2002
DOI: 10.1081/ddc-120003451
|View full text |Cite
|
Sign up to set email alerts
|

19F Solid-State NMR Spectroscopic Investigation of Crystalline and Amorphous Forms of a Selective Muscarinic M3Receptor Antagonist, in Both Bulk and Pharmaceutical Dosage Form Samples

Abstract: The purpose of the following investigation was to display the utility of 19F solid-state nuclear magnetic resonance (NMR) in both distinguishing between solid forms of a selective muscarinic M3 receptor antagonist and characterizing the active pharmaceutical ingredient in low-dose tablets. Ambient- and elevated-temperature solid-state 19F fast (15 kHz) magic-angle spinning (MAS) NMR experiments were employed to obtain desired spectral resolution in this system. Ambient sample temperature combined with rotor fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…as an alternative method for the structural analysis of APIs. 11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our research group and others have demonstrated that 35 Cl SSNMR can function as a non-destructive structural probe and a technique for polymorph identification and screening of hydrochloride (HCl) APIs. [36][37][38][39] Given that more than 50% of APIs are produced as HCl salts, 40 the widespread use of 35 Cl SSNMR in quality assurance, and research and development departments of pharmaceutical companies is promising.…”
Section: Introductionmentioning
confidence: 99%
“…as an alternative method for the structural analysis of APIs. 11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our research group and others have demonstrated that 35 Cl SSNMR can function as a non-destructive structural probe and a technique for polymorph identification and screening of hydrochloride (HCl) APIs. [36][37][38][39] Given that more than 50% of APIs are produced as HCl salts, 40 the widespread use of 35 Cl SSNMR in quality assurance, and research and development departments of pharmaceutical companies is promising.…”
Section: Introductionmentioning
confidence: 99%
“…punched oral tablets) without difficulty. 191,192 A 1 H-detected 2D 13 C-1 H CP-HETCOR experiment, performed at n r ¼ 40 kHz with a 1.6 mm probe and using the MISSISSIPPI (multiple intense solvent suppression intended for sensitive spectroscopic investigation of protonated proteins instantly) pulse sequence to suppress strong 1 H signals, was shown rapidly and specifically to detect ibuprofen and acetaminophen APIs in high drug load (460%) formulations. 225 A 2D 1 H DQ experiment performed with homonuclear 1 H decoupling (also referred to as the DQ-CRAMPS experiment, where CRAMPS is an acronym for combined rotation and multiple pulse sequence) also successfully detected the API form in formulations, with additional specificity available from the DQ dimension.…”
Section: Formulations and Dispersions Of Drugsmentioning
confidence: 99%
“…189,190 Basic 1D 19 F CP-MAS and DP-MAS experiments have been shown to be specific and extremely sensitive in the analysis of fluorinated drug polymorphs. 191,192 Aryl fluorides generally offer the widest chemical shift range of the different fluorinated functional groups found in drugs. 14 Trifluoromethyl groups rotate in crystalline organic solids and the consequent chemical shift averaging tends to offer less specificity for discriminating between polymorphs, 34 but they are still highly sensitive and useful when present in an API.…”
Section: 90mentioning
confidence: 99%
“…For instance, 19 F is often found in APIs but not excipients offering the opportunity for excellent discriminating power in multicomponent systems. Wenslow used 19 F ssNMR to successfully discriminate between the amorphous and crystalline forms of a muscarinic M3 receptor antagonist after formulation into a tablet at 2 wt% (Wenslow 2002), highlighting both the sensitivity and the ability to easily discriminate in dilute multicomponent mixtures. With respect to mobility measurements, ssNMR offers access to molecular motions ranging from 10 À11 to 10 3 s via relaxation measurements and 10 À5 to 10 À10 cm 2 /s via diffusion measurements (Ediger et al 1996).…”
Section: Solid-state Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%